2020
DOI: 10.1063/5.0030508
|View full text |Cite
|
Sign up to set email alerts
|

Fine structures of acoustic emission spectra: How to separate dislocation movements and entanglements in 316L stainless steel

Abstract: Intermittent avalanches in a multitude of materials are characterized by acoustic emission, AE, where local events lead to strain relaxations and generate shock waves (so-called “jerks”), which are measured at the sample surface. The bane of this approach is that several avalanche mechanisms may contribute to the same AE spectrum so that a detailed analysis of each individual contribution becomes virtually impossible. It is, hence, essential to develop tools to separate signals from different dynamical process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Since our acoustic activity was very low at high temperatures, more efforts are needed to clear up the reason of the obtained small value of ε (i.e., whether it is caused by the presence of different types of AE signals and/or if this is due to the combination of wild and mild fluctuations) [ 22 ]. Another option can be the application of the recently published method [ 56 ] to separate signals from different dynamical processes.…”
Section: Resultsmentioning
confidence: 99%
“…Since our acoustic activity was very low at high temperatures, more efforts are needed to clear up the reason of the obtained small value of ε (i.e., whether it is caused by the presence of different types of AE signals and/or if this is due to the combination of wild and mild fluctuations) [ 22 ]. Another option can be the application of the recently published method [ 56 ] to separate signals from different dynamical processes.…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [ 43 ] Copyright 2021, Elsevier. b) TEM image after tension (tensile strain: ≈70%) shows that martensites and dislocation microstructures coexist.…”
Section: Resultsmentioning
confidence: 99%
“…Chen and her collaborators have demonstrated how to separate dislocation moves and entanglements in 316 L stainless steel. They showed that the main difference between the two mechanisms is the average duration for each type of avalanche [74].…”
Section: Avalanche Mixingmentioning
confidence: 99%